Kadın cinayetleri Muş-Bitlis örneği - Ateş, Sultan (Muş Alparslan Üniversitesi, 2020)
Kadın cinayetleri, toplum sağlığını olumsuz yönde etkileyen ve tüm insanlığın ortak sorunu olarak varlığını sürdüren bir olgudur. Muş ve Bitlis illerinde namus-töre ve arzu cinayetleri ekseninde incelenen kadın cinayetlerinde toplumsal yapının (kültür, ataerkil aile yapıları, toplumsal cinsiyet rolleri) etkileri irdelenmiştir. Bu çalışmada kullanılan bilgiler, Muş ve Bitlis adliyelerinin UYAP sisteminin iddianamelerinden toplanan dokuz kadın cinayeti vakasına aittir. Adliyelerden alınan iddianameler ışığında yapılan incelemede kadın cinayetleri üzerinde toplumsal yapının etkilerini görmek mümkündür. Toplum tarafından namus ve tutkuya verilen anlam kadın odaklıdır. Başka bir deyişle, kadın cinayetleri ve bu çalışmanın temel bir nesnesi olan kadınlar, toplumda namus ve tutku kavramlarının eş anlamlıları olarak algılanmaktadırlar. Bu kapsamda çalışmada yer alan vakalarda söz konusu terimlerin anlamıyla uyuşmakta olan cinayetler tespit edilmiştir

Femicides or feminicides are the phenomena influencing the health of society adversely and continues to exist as a common problem of all humanity. In this study, the effects of social structure (e.g., culture, patriarchal family structure, and roles of social gender) over femicides were examined on the basis of honor killings and crimes of passion in the provinces of Muş (five cases) and Bitlis (four cases), Turkey. The information used in this study, belonging to nine femicides cases collected from the indictment records of National Judiciary Informatics System (UYAP) of Muş and Bitlis court houses. Based on the investigations, it is possible to see the effects of social structure over femicides in the light of indictments obtained from court houses. The meaning assigned to the honor and passion by the society is female-oriented. Put it another way, the females as a basic object of the femicides and of this study are perceived as synonym terms of honor and of passion by the society. In this context, the femicides congruent to the meaning of terms of honor and passion were determined in the case studies in this work
Women murders Muş-Bitlis sample
Keywords: Siyasal Bilimler; Political Science; Bitlis; Bitlis; Cinayet; Murder; Kadınlar; Women; Muş; Muş; Toplumsal cinsiyet; Gender